2014
DOI: 10.1631/jzus.b1300088
|View full text |Cite
|
Sign up to set email alerts
|

Association of matrix metalloproteinase-9 C1562T polymorphism and coronary artery disease: a meta-analysis

Abstract: Abstract:Objective: Many investigations have studied the associations between matrix metalloproteinase-9 (MMP-9) C1562T polymorphisms and coronary artery disease (CAD). However, the conclusions of these studies were inconsistent. Therefore, this study was aimed at clarifying the association between MMP-9 C1562T polymorphisms and CAD in a large-scale meta-analysis. Methods: The PubMed and Embase databases were retrieved to collect all publications on the association between MMP-9 C1562T polymorphisms and CAD. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
1
26
0
1
Order By: Relevance
“…Alp et al (2009) and Ghaderian et al (2010) did not find a significant association between MMP-9 rs3918242 genetic variation and development of coronary artery disease and myocardial infarction in Turkish and Chinese population. Two recent meta-analysis studies reported that the MMP-9 rs3918242 genetic factors may have association with the risk of coronary artery disease in Asian populations (Wang and Shi, 2014;Zhang et al, 2014). In our study, we found that the TT and CT genotypes and T allele of MMP-9 rs3918242 could influence the development of coronary artery disease in a Chinese population.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Alp et al (2009) and Ghaderian et al (2010) did not find a significant association between MMP-9 rs3918242 genetic variation and development of coronary artery disease and myocardial infarction in Turkish and Chinese population. Two recent meta-analysis studies reported that the MMP-9 rs3918242 genetic factors may have association with the risk of coronary artery disease in Asian populations (Wang and Shi, 2014;Zhang et al, 2014). In our study, we found that the TT and CT genotypes and T allele of MMP-9 rs3918242 could influence the development of coronary artery disease in a Chinese population.…”
Section: Discussionsupporting
confidence: 61%
“…Three main polymorphisms were observed in the promoter, coding and untranslated region of MMP-9 (Zhang et al, 1999). The MMP-9 rs3918242 polymorphism (C ® T) is located at the promoter region, and previous studies have reported that the MMP-9 rs3918242 gene polymorphism plays an important role in the development of coronary artery diseases, but the results are inconclusive (Mishra et al, 2012;Opstad et al, 2013;Xu et al, 2013;Opstad et al, 2014;Wang and Shi, 2014;Zhang et al, 2014). Therefore, we carried out a case-control study to assess the role of one single nucleotide polymorphism (SNP) of MMP-9 rs3918242 in the development of coronary artery disease.…”
Section: Introductionmentioning
confidence: 98%
“…In another study on Iranian population, Ghaderian et al also failed to indicate that MMP-9 T allele had www.scienceasia.org an association with increasing risk of developing AMI 15 . Although these studies showed inconsistent results, a plausible explanation may be drawn from the study of Wang and Shi 21 . Using meta-analysis of 16 case-control studies, the authors suggested that MMP-9 1562C>T polymorphism was an occurrence of coronary artery diseases in the East Asian but not in the West Asian 21 .…”
Section: Discussionmentioning
confidence: 98%
“…Using meta-analysis of 16 case-control studies, the authors suggested that MMP-9 1562C>T polymorphism was an occurrence of coronary artery diseases in the East Asian but not in the West Asian 21 . This difference could be explained by the genetic specificity of population ethnicity 18,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms by which coexistence of CAD and ARAS is associated with HFpEF are under investigation (Groban and Kitzman, 2010;Wang and Shi, 2014). The progressive increase in cardiac diastolic dysfunction leading to a worsening of CAD and ARAS is partly explained by factors such as increased afterload, renal hypertension resulting from ARAS, myocardial ischemia, overactivation of RAAS, and inflammation (Ding et al, 2014).…”
Section: Discussionmentioning
confidence: 99%